ON THE CONCEPT AND LIMITS OF THE RIGHT OF RETENTION (Journal of actual problems of jurisprudence, 2019)
Based on the above, we conclude that the right of retention is limited in time. At7 this conflict is very likely to prevent the conclusion of an agreement under the rules of paragraph 1 of article 335 of the civil code.126 Kazuu khabarshysy. Zan seriesi. № 3 (55). Two thousand tenthis right to retain the thing arises from the creditor at the time of delay of the debtor, the momentthe occurrence of the right to foreclose on the thing held does not coincide with the occurrence ofthe right of retention and should be determined (and in the event of a dispute – and evaluated by the court) onbased on the criteria of good faith and reasonableness. Stop both components of the rightwithholding at the same time-with the expiration of the Statute of limitations on the principal obligation.